2021
DOI: 10.2106/jbjs.21.00346
|View full text |Cite
|
Sign up to set email alerts
|

Unicompartmental Knee Arthroplasty: Survivorship and Risk Factors for Revision

Abstract: Background:Operative management for end-stage knee osteoarthritis (OA) primarily consists of arthroplasty. Total knee arthroplasty (TKA) is the so-called gold standard for multicompartmental OA. In selected patients, specifically those with unicompartmental OA and no definite contraindications, realignment osteotomies and unicompartmental knee arthroplasty (UKA) are viable options. UKA offers several advantages over TKA, including preservation of both cruciate ligaments, faster recovery, and less osseous resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…In the present study, we verified that excessive protrusion of the tibial implant could irritate the medial soft tissue and affect the functional prognosis of the patient [11,15]. All patients received a 94.9% survival rate during the follow up time, which is similar to the five-year revision rates of 87.5-90.5% reported by Moore et al and Ekhtiari et al [10,16]. Nevertheless, the postoperative revision rate in the major overhang group was a striking 20.9%, with the reasons for revision being bearing dislocation and aseptic loosening, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, we verified that excessive protrusion of the tibial implant could irritate the medial soft tissue and affect the functional prognosis of the patient [11,15]. All patients received a 94.9% survival rate during the follow up time, which is similar to the five-year revision rates of 87.5-90.5% reported by Moore et al and Ekhtiari et al [10,16]. Nevertheless, the postoperative revision rate in the major overhang group was a striking 20.9%, with the reasons for revision being bearing dislocation and aseptic loosening, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Although UKA has many advantages, the literature [2,[6][7][8] has shown that UKA has a higher revision rate than total knee arthroplasty (TKA). Common reasons for revision in UKA are knee pain, aseptic loosening of the component, progression of contralateral knee osteoarthritis, and bearing wear/dislocation [9,10]. However, fewer researchers have focused on the relationship between tibial component position and postoperative revision rates.…”
Section: Introductionmentioning
confidence: 99%
“…At a minimum follow-up of 10 years, a large population database study demonstrated that UKA survivorship was >80%, and mechanical loosening was responsible for 83.4% of revisions. Failure risk factors were younger age, diabetes, male sex, and cementless fixation 13 . In a retrospective study of lateral UKA, survivorship rates in patients ≥60 years of age were 98% at 5 years and 96% at 10 years.…”
Section: Ukamentioning
confidence: 99%
“…However, UKA has a higher revision rate compared with total knee arthroplasty (TKA) 3-5 . Further research on risk factors, such as implant design and patient indications, and on reasons for revision 6,7 is needed to understand the higher risk of revision associated with UKA.…”
mentioning
confidence: 99%
“…There is also ongoing debate regarding the ideal UKA patient profile [15][16][17] . While several studies have reported lower UKA survivorship in younger patients 6,7 and those with a higher body mass index (BMI) 18,19 , others have reported contrasting results 7,20,21 .…”
mentioning
confidence: 99%